Development of Technological Options for the Use of Various Wastes as Alternative Energy Sources Based on Multicomponent Compositions of Solid Fuels - A. N. Pekhota; B. M. Khrustalev; V. P. Golubev; Thuy Nga Nguyen; Minh Phap Vu (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2024)
The article considers promising areas for solving problems of energy and resource conservation, as well as issues of rational use of natural and secondary resources generated in industrial and communal activities. The aspects of research and development of technological options for the use of various wastes based on multicomponent compositions of solid fuels as alternative energy sources are presented. Also presented are the main stages of the developed and applied technologies for briquetting and incineration of multicomponent mixtures based on various combustible waste. The developed algorithm for solving the problem under consideration which makes it possible to rationally use substandard combustible industrial municipal waste to obtain multicomponent solid fuel that meets the quality criteria for energy and environmental indicators is reviewed. The results of the applied research directly related to the qualitative assessment of multicomponent briquetted fuels and facilitating achievement of the best production and consumer indicators values of energy quality and environmental friendliness are presented.